Сучасний стан, проблемні питання та практичні механізми підвищення ефективності використання енергетичних ресурсів в комунальному секторі України - Novoseltsev A.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2002)
Energy efficiency improvement environment, problems and tools to overcome them in communal sector of Ukraine's economy are considered at the case study of municipal water/wastewater and heating utilities. Peculiar properties of Energy Performance Contracting using to finance energy saving projects through Energy Service Companies are analyzed in detail.